SEXUAL ACTIVITY OF KARAKUL SHEEP OF DIFFERENT AGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The systematic use of only highly productive rams for mating, which transfer their valuable qualities to the offspring well, is the most important condition for improving the qualitative composition of the herd and increasing its productivity.The use of animals at an early age is of great importance for the rapid change of their generations and acceleration of the pace of breeding work. This work is devoted to the study of the sexual activity of rams of different ages.